GalNAc Conjugation Attenuates the Cytotoxicity of Antisense Oligonucleotide Drugs in Renal Tubular Cells - Sabine Sewing; Marcel Gubler; Régine Gérard; Blandine Avignon; Yasmin Mueller; Annamaria Braendli-Baiocco; Marielle Odin; Annie Moisan (Elsevier, 2019)
Targeted delivery of antisense oligonucleotide (AON) drugs is a promising strategy to increase their concentration in the desired tissues and cell types while reducing access to other organs. Conjugation of AONs to N-acetylgalactosamine (GalNAc) has been shown to efficiently shift their biodistribution toward the liver via high-affinity binding to the asialoglycoprotein receptor (ASGPR) expressed at the surface of hepatocytes. Nevertheless, GalNAc conjugation does not prevent accumulation of AONs in the kidney cortex, and GalNAc-conjugated AONs might cause kidney toxicities, for example, under conditions of ASGPR saturation. Here, we investigated the nephrotoxicity potential of GalNAc-conjugated AONs by in vitro profiling of AON libraries in renal proximal tubule epithelial cells (PTECs) and in vivo testing of selected candidates. Whereas GalNAc-conjugated AONs appeared generally innocuous to PTECs, some caused mild-to-moderate nephrotoxicity in rats. Interestingly, the in vivo kidney liabilities could be recapitulated in vitro by treating PTECs with the unconjugated (or naked) parental AONs. An in vitro mechanistic study revealed that GalNAc conjugation attenuated AON-induced renal cell toxicity despite intracellular accumulation similar to that of naked AONs and independent of target knockdown. Overall, our in vitro findings reveal ASGPR-independent properties of GalNAc AONs that confer a favorable safety profile at the cellular level, which may variably translate in vivo due to catabolic transformation of circulating AONs. Keywords: antisense oligonucleotide, targeted delivery, kidney, ASGPR, toxicity